Investigating the Prevailing Hydrodynamics Around a Cold-Water Coral Colony Using a Physical and a Numerical Approach - Bartzke, Gerhard; Siemann, Lennart; Büssing, Robert; Nardone, Paride; Koll, Katinka; Hebbeln, Dierk; Huhn, Katrin (Frontiers in Marine Science, 2021)
Framework-forming cold-water corals provide a refuge for numerous organisms and, consequently, the ecosystems formed by these corals can be considered as impressive deep-sea biodiversity hotspots. If suitable environmental conditions for coral growth persist over sufficiently long periods of time in equilibrium with continuous sediment input, substantial accumulations of coral mound deposits consisting of coral fragments and baffled sediments can form. Although this conceptual approach is widely accepted, little is known about the prevailing hydrodynamics in their close proximity, which potentially affect sedimentation patterns. In order to refine the current understanding about the hydrodynamic mechanisms in the direct vicinity of a model cold-water coral colony, a twofold approach of a laboratory flume experiment and a numerical model was set up. In both approaches the flow dynamics around a simplified cold-water coral colony used as current obstacle were investigated. The flow measurements of the flume provided a dataset that served as the basis for validation of the numerical model. The numerical model revealed data from the vicinity of the simplified cold-water coral such as the pressure field, velocity field, or the turbulent kinetic energy in high resolution. Features of the flow like the turbulent wake and streamlines were also processed to provide a more complete picture of the flow that passes the simplified cold-water coral colony. The results show that a cold-water coral colony strongly affects the flow field and eventually the sediment dynamics. The observed decrease in flow velocities around the cold water-coral hints to a decrease in the sediment carrying potential of the flowing water with consequences for sediment deposition.